Two new species of the genus Dactyloscirus (Acari: Prostigmata: Bdelloidea: Cunaxidae) from Sumatra, Indonesia, with a key to known species - Corpuz-Raros, Leonila A.; Naredo, Jeremy C.b.; Lit, Ireneo L. Jr; Caasi-Lit, Merdelyn T. (Zootaxa, 2022)
Two new species of predatory cunaxid mites belonging to the genus Dactyloscirus are described: Dactyloscirus sumatranus Corpuz-Raros and Naredo sp. n. and D. ladangjagung Corpuz-Raros and Lit sp. n. Both inhabit soil in corn fields in Sumatra Island, Indonesia. Dactyloscirus. sumatranus closely resembles D. dolichosetosus Den Heyer, 1979, but differs in having the basal half of chelicera strongly inflated, about four times thicker than in the distal half (vs. slender and gradually tapered), hysterosomal setae f1 and h1 at least twice as long as the anterior pairs c1-e1 (vs. only slightly longer), and famulus of tarsus I only ¾ the length of the closely associated asl (vs. longer). Dactyloscirus ladangjagung resembles D. hoffmannae Swift, 1996, but differs by the number of setae on some leg segments, namely, basifemora (5-5-3-2 vs. 5-5-3-1 sts) and tibiae (5-5-5-4 vs. 4-5-4-2 sts), and in having setae g4 the longest of genital setae (vs. setae g3). An updated key to 30 known Dactyloscirus species is provided.